Stoichiometric quantification of spatially dense assemblies with qPAINT. Issue 26 (23rd May 2019) - Baker, Matthew A. B.; Nieves, Daniel J.; Hilzenrat, Geva; Berengut, Jonathan F.; Gaus, Katharina; Lee, Lawrence K.
Abstract : DNA qPAINT can be used to quantify the stoichiometry of dense arrays of molecules separated by as little as 3 nm. Abstract : Quantitative PAINT (qPAINT) is a useful method for counting well-separated molecules within nanoscale assemblies. But whether cross-reactivity in densely-packed arrangements perturbs measurements is unknown. Here we establish that qPAINT measurements are robust even when target molecules are separated by as little as 3 nm, sufficiently close that single-stranded DNA binding sites can interact.